Community Service: Implementation of Avocado Sponge Cake Making for Agricultural Product Diversification - Intania Cicilia Dewi; Mannan Ni’mal Khasbi; Hannum Maziyyatun Nihayah; Elly Lailatul Mahmudah; Ilham Himawan Rosadi; Chusnul Adib Achmad (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
Diversification of agricultural products is one strategy to increase the added value and competitiveness of local commodities. Avocado (Persea americana) is a tropical fruit that is rich in nutrients, such as healthy fats, fiber, vitamins and minerals. However, the use of avocados in Indonesia is still limited to fresh consumption and simple processing. This research aims to develop an innovative product in the form of avocado-based sponge cake as an effort to diversify agricultural products. The method used includes organoleptic testing. The research results show that the use of avocado in making sponge cake can improve the soft texture, distinctive aroma, color and unique taste. Organoleptic tests show a good level of consumer acceptance with an average score of above 50% in the aspects of taste, color and texture. Apart from that, nutritional analysis shows that avocado cake has a higher content of healthy fats and fiber than conventional cake. Implementation of this product has the potential to open up new market opportunities and provide added value for local avocado farmers.